Uncovering the link between celiac disease and hypopituitarism: a case report and review of literature - Hameed Haidar Khan; Imran Ullah; Javeria Rufaq; Qaiser Wadood; Imad Majeed; Salman Khan (The Egyptian Journal of Internal Medicine, 2023)
Abstract Background Celiac disease, an autoimmune condition triggered by gluten-containing diet, is known to primarily manifest as intestinal symptoms, but can also lead to extraintestinal complications, including endocrine abnormalities and autoimmune disorders. This case report outlines a patient with celiac disease who developed hypopituitarism and explores the possible pathophysiological links between these two conditions. Case presentation We report a case of a 19-year-old female who presented with lethargy, weakness, delayed menarche, and failure to thrive. Subsequent investigations revealed microcytic anemia with decreased serum ferritin and vitamin D levels. Following the identification of abnormal bone age on X-ray, a hormonal profile was requested which revealed panhypopituitarism. After undergoing a diagnostic workup for her gastrointestinal symptoms, she was eventually diagnosed with celiac disease, and her symptoms improved significantly following gluten restriction. Conclusion Panhypopituitarism has a possible association with celiac disease, and this case highlights the importance of close monitoring and appropriate management to prevent long-term health consequences. Additional research is necessary to gain a comprehensive understanding of the link between celiac disease and endocrine disorders.